Effectiveness of bevacizumab- and pemetrexed-cisplatin treatment for patients with advanced non-squamous non-small cell lung cancer - Nuijten, Marcus Johannes Catharina; Heigener, David F.; Bischoff, Helge; Chouaid, Christos; Vergnenègre, Alain; de Castro Carpeño, Javier; Aultman, Rick; Walzer, Stefan; Siebert, Uwe (Lung cancer, 2010)
The new targeted agent bevacizumab in combination with cisplatin and gemcitabine, and a third generation chemotherapy, pemetrexed, combined with cisplatin, are approved as first-line treatment for patients with advanced nonsquamous non-small cell lung cancer (NSCLC). As no head-to-head comparison of these treatments exists, this study aimed to compare the effectiveness of the two treatments using an indirect treatment comparison approach. An indirect comparison on progression-free survival (PFS) was performed for two relevant randomised controlled trials using a well-accepted adjusted indirect comparison method. The results were used in a statistical disease model (Markov model) to extrapolate the long-term effectiveness of the two treatments. A hazard ratio of 0.83 for PFS for bevacizumab plus cisplatin and gemcitabine, was calculated suggesting that this treatment is associated with a 17% lower risk of disease progression and death compared with pemetrexed plus cisplatin treatment. The Markov model predicted that bevacizumab plus cisplatin and gemcitabine resulted in 2.5 months additional PFS and overall survival compared with pemetrexed plus cisplatin. Based on this analysis bevacizumab plus cisplatin and gemcitabine is more effective than pemetrexed plus cisplatin for patients with advanced non-squamous NSCLC and should be considered as one of the preferred targeted treatments of choice for these patients.